Effects of terlipressin infusion on blood loss and transfusion needs during liver resection: A randomised trial. Issue 1 (5th August 2018) - Abbas, Mostafa S.; Mohamed, Khaled S.; Ibraheim, Osama A.; Taha, Ahmed M.; Ibraheem, Tameem M.; Fadel, Bashir A.; Elawamy, Abdelraheem; Abbas, Ahmed M.
Abstract : Background: Blood loss and perioperative blood transfusion requirements affect the long‐term survival after liver resection for malignant tumours. Terlipressin is a synthetic vasopressin analogue with relative specificity for the splanchnic circulation where it causes vasoconstriction with subsequent reduction of blood loss during abdominal surgeries. We tried to examine the impact of terlipressin on blood loss and blood transfusion needs during liver resection. Methods: In this randomised, double‐blind placebo‐controlled trial 84 patients scheduled for major liver resections were randomly assigned to receive either terlipressin at the onset of surgery as an initial bolus dose of (1 mg over 30 minutes) followed by a continuous infusion of 2 μg/kg/h throughout the procedure (Terlipressin group) or the same volume and rate of 0.9% saline (Placebo group).The primary outcome was the amount of intra‐operative blood loss. Results: The mean (SD) of the amount of intra‐operative blood loss was 1351 (887) in the terlipressin group versus 1892 (889) mL in the placebo group ( P = 0.006). Thirteen (30%) patients received blood transfusion in the terlipressin group compared with t27 (64.2%) in the placebo group ( P = 0.002) with a statistically significant difference in the median (range) number of the transfused units of packed RBCs [0 (0‐5) units and 1 (0‐6) units in the two groups respectively; P = 0.001]. Conclusion: Terlipressin infusion during major liver resection was associated with less bleeding compared to placebo. More studies are required to confirm our results especially in patients with normal portal pressure.